Primary Stability of Self-Drilling and Self-Tapping Mini-Implant in Tibia of Diabetes-Induced Rabbits - Jea-Beom Park; Eun-Young Kim; Janghyun Paek; Yoon-Ah Kook; Do-Min Jeong; Il-Sik Cho; Gerald Nelson (International Journal of Dentistry)
Objective. This study aimed to evaluate effects of type 1 diabetes mellitus and mini-implant placement method on the primary stability of mini-implants by comparing mechanical stability and microstructural/histological differences. Methods. After 4 weeks of diabetic induction, 48 mini-implants (24 self-tapping and 24 self-drilling implants) were placed on the tibia of 6 diabetic and 6 normal rabbits. After 4 weeks, the rabbits were sacrificed. Insertion torque, removal torque, insertion energy, and removal energy were measured with a surgical engine on 8 rabbits. Remaining 4 rabbits were analyzed by microcomputed tomography (micro-CT) and bone histomorphometry. Results. Total insertion energy was higher in self-drilling groups than self-tapping groups in both control and diabetic groups. Diabetic groups had more trabecular separation in bone marrow than the control groups in both SD and ST groups. Micro-CT analysis showed deterioration of bone quality in tibia especially in bone marrow of diabetic rabbits. However, there was no statistically significant correlation between self-drilling and self-tapping group for the remaining measurements in both control and diabetic groups. Conclusions. Type 1 diabetes mellitus and placement method of mini-implant did not affect primary stability of mini-implants.